EFFECT OF AMYGDALUS EBURNEA ON THIRD-DEGREE BURNS IN RATS AND COMPARISON WITH SILVER SULFADIAZINE OINTMENT - Rezaeifar, Mehdi; Rezaeifar, Maryam (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Amygdalus eburnea is a perennial herb that has been valued for its important biological perspectives and it has been used to treat the burn. This study aims to evaluate wound healing activity of A. eburnea extract compared with silver sulfadiazine (a synthetic burn ointment) for treating the induced third-degree burn in rat. Methods: In this study, a deep, third-degree burn wound was induced by a hot plate warmed 5 minutes within boiling water and placed for 3 seconds on the skin. The shell root of A. eburnea an Iranian medicinal herb is investigated on its wound healing activity in comparison with silver sulfadiazine ointment as the standard treatment for burn wound in rats. Results: Our results demonstrated that A. eburnea can be an effective treatment for third-degree burns. Advanced clinical and pharmaceutical studies are recommended to the production of novel natural drugs for burn wound treatment. Conclusion: A. eburnea can be an effective treatment for third-degree burns. Advanced clinical and pharmaceutical studies are recommended to the production of novel natural drugs for burn wound treatment.